α-D-glucopyranosyl isothiocyanate의 기능화에 의한 2-Phenylimino-1,3-thiazoline 유도체의 합성 - 한호규; 마혜덕; 신동윤; 한민수; 남기달 (한국키틴키토산학회, 2009)
As a part of fuctionalization of α-D-glucopyranosyl isothiocyanate 15, 2-(2-phenylimino-4-thioureido-1,3-thiazoline)-α-D-glucopyranose derivatives 16 were synthesized by the reaction of α-D-glucopyranosyl isothiocyanate 15 with 4-aminomethyl-1,3-thiazoline derivatives 6. An optimal reaction condition for a synthesis of α-D-glucosamine hydrogen chloride 12 was established by the reaction of D-glucosamine sequentially with diethylethoxymethylene malonate, acetic anhydride, and chlorine. α-D-glucopyranosyl isothiocyanate 15 was prepared from the dehydrochlorination of α-D-glucosamine hydrogen chloride 12 and then treated with thiophogene. Bromination of 2-keto phthalimide which was obtained from the reaction of phthalimide potassium salts with chloroacetone gave 2-keto bromophthalimide 3 in high yield. This was reacted with an equal molar equivalent of N-methyl-N'-phenylthiourea derivatives 4, which were prepared independently to give the corresponding 4-phthalimidyl-1,3-thiazoline 5 in over 80% yield. 4-Aminomethyl-1,3-thiazoline intermediates 6 were synthesized by a deprotection of phthalimidyl moiety of 5 by the action of hydrazine, methylamine or ethanolamine, of which structures were confirmed by their 1H NMR spectra. Thus, the protons of amino methylene, 3-methyl and 5-vinyl showed in range of δ 1.3-1.8 ppm, 3.4-3.7 ppm and 5.7-5.8 ppm respectively without influence of functional group of the side chain. The characteristic doublet at 6.36 ppm with J1,2 3.3Hz in the 1H NMR of the target molecule α-anomer 16 confirmed the sterochemistry of the compound. The synthesized compounds would be contributed a combinatorial chemistry or a chemical library for an exploration of new biological active material.